THE EFFECT OF INQUIRY TRAINING MODEL ASSISTED BY VIDEO TO LEARNING OUTCOMES ON MEASUREMENT TOPIC - Pandi Sihaloho; Makmur Sirait (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2019)
The study aims to determine students learning outcomes during learning by using inquiry training learning models. This type of research is a quasiexperiment. The population in this study were all student of class X semester I consisting four class MIA. The sample of this study was taken two classes, namely class X MIA-1 as an experimental class total 35 students and class X MIA-2 as a control class total 35 students who were determined using class random sampling. The instrument used to determine student learning outcomes in the form of multiple choices obtained the number of valid questions as many as 15 items. To test the hypothesis used a different test (t-test). The research data shows the average score of experiment class pretest 33.7 with standard deviation 13.9, posttest 75.6 with standard deviation 12.4, while the average score of the pretest control class is 35.2 with standard deviation 13.7, posttest 61.5 with standard deviation 12.3. Both classes are normally distributed and the variance of both classes is homogeneous. The results of testing the hypothesis using the t-test, there is an effect of the inquiry training model on student learning outcomes in the subject matter of measurement.